Greening Global Value Chains : Innovation and the International Diffusion of Technologies and knowledge - Glachant, Matthieu (World Bank, Washington, DC, 2013)
Using novel data on patents, trade of equipment goods, and foreign direct investments and insights from the economic literature, the paper seeks to lay out the state of knowledge on the role of innovation and the diffusion of technologies in the greening of global value chains as well as some of the main policy issues. A special emphasis is put on developing countries -- distinguishing emerging economies and least-developed countries -- and on climate-mitigation technologies. Emerging economies are already reasonably well integrated in the global economy. As a consequence, technologies flow in through the imports of capital goods and local investments by multinational enterprises owning technologies. Pushing further technology transfer requires strengthening intellectual property rights, lowering barriers to trade and investments and improving technological absorptive capacities. In contrast, their role in innovation is limited. Standard tools of innovation policy - public research and development, public support to private research and development, better access to finance - should develop. But studies also suggest that governments should introduce more stringent environmental policies with proper enforcement at home to go beyond the adoption of foreign technologies. The situation of least-developed countries is very different: they do not import green technologies and low barriers to trade and foreign direct investment or strict intellectual property rights are unlikely to trigger technology transfer. In these countries, the focus should be on building technological capacities.